IMPLEMENTASI KEGIATAN BAZAR UMKM SEBAGAI UPAYA DALAM MEMPERKUAT KETAHANAN PANGAN DI KELURAHAN AMBORAWANG DARAT - Yanzil Azizil Yudaruddin; Siti Della Ananda Lesmana; Dika Karlida Sari; Ranita Ramadhani; Juwari Juwari (Fakultas Ekonomi Universitas Balikpapan, 2023)
Factors causing the food crisis in Amboawang Darat Village include, many productive workers who choose to work in offices, lack of public knowledge in MSME management so that their potential cannot be maximized, and damage to agricultural land due to mining activities around the land area. Based on the conditions in the field and seeing the condition of MSMEs in the Ambowang Darat Village, the researchers carried out bazaar activities as a strategy to strengthen food security. The research method used is descriptive qualitative. The data in this study uses primary data and secondary data. Data collection techniques through the process of observation, interviews with MSME actors involved in implementing the MSME bazaar, and documentation. The approach used by researchers is a participatory approach because they are directly involved in MSME bazaar activities. The implementation of the MSME bazaar has had various positive impacts on the community in the Ambowang Darat Village, including; 1) increasing product sales through MSME bazaar stands, 2) MSME products are better known in the Ambowang Darat Village, 3) the public can carry out promotions so that the market share becomes wider.